The Effect of Islamic Marketing Mix, Service Quality and Product Quality on Consumer Loyalty of Microfinance Institution: Does Perceived Value act as mediator? - Mondir, Mohamad; Rahma, Siti Habibatur (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The competition among financial institutions for customers is fierce. Moreover, the majority of people in Indonesia prefer giant financial institutions that are considered more competent and safe in their financial affairs. This makes some microfinance institutions such as BMT NU East Java have to try very hard in getting customers. BMT NU East Java must formulate the right strategy to get new customers and make customers loyal. This research aims to gain a great understanding on how consumer is loyal to microfinance institution and which one from Islamic marketing mix, service quality, product quality and perceived value, became variable that influence consumer loyalty. The research is quantitative research and conduct at BMT NU Jawa Timur. The data is collected from 200 consumer of BMT NU. This study is quantitative research with 200 BMT NU Jawa Timur customer samples. It uses non-probability sampling and the Data collected will be analyzed with the help of SPSS software to get statistical techniques for correlation and regression (validity test, reliability test, classic assumption test, path analysis, t-test, trimming test. The result shows that service quality and product quality were variable which most affect consumer loyalty. Perceived value also can mediate Islamic Marketing mix, service quality, and product quality variables on customer loyalty. In this case, the loyalty of consumer can be created with giving more responsiveness and empathy to consumer. It also can be created with great reliability and performance that exist in the microfinance product. The results of this research can be applied by BMT NU East Java by strengthening services and financial products to gain customer trust. This research can be a reference for other researchers who want to research Islamic microfinance by providing additional variables and different points of view